Interethnic variability in CYP2D6, CYP2C9, and CYP2C19 genes and predicted drug metabolism phenotypes among 6060 Ibero- and native americans: RIBEF-CEIBA Consortium Report on population pharmacogenomics - Naranjo, María Eugenia G. (2018)
Fil: Naranjo, María Eugenia G. RIBEF Ibero-American Network of Pharmacogenetics and Pharmacogenomics; España